Nickel-zinc ferrite material as well as preparation method and application thereof

By adjusting the component ratio and process steps of nickel-zinc ferrite materials, the problem that existing materials are difficult to have high magnetic permeability, Curie temperature, saturated magnetic induction strength and low high frequency loss is solved, and the preparation and application of nickel-zinc ferrite materials with excellent comprehensive performance is realized.

CN119661211AActive Publication Date: 2025-03-21HENGDIAN GRP DMEGC MAGNETICS CO LTD +1

Patent Information

Application Number
CN202411742600.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-03-21
Estimated Expiration
2044-11-29

AI Technical Summary

Technical Problem

Existing nickel-zinc ferrite materials are difficult to have the properties of high permeability, Curie temperature, saturated magnetic induction strength and low high frequency loss.

Method used

By adjusting the ratio of main and secondary components, specifically including the mass percentage of Fe2O3, NiO, ZnO, CuO, etc., and adding auxiliary components such as Al2O3, SiO2 and MnO2, the process steps of sand mill mixing, drying, prefixing, granulation and sintering are used to prepare nickel-zinc ferrite materials with excellent comprehensive performance.

Benefits of technology

The comprehensive performance of magnetic permeability of 200±25%, Curie temperature exceeding 300℃, saturated magnetic induction intensity exceeding 485mT and relative loss factor less than 32 (f=1MHz) is achieved. It is suitable for high-frequency inductors, filters, transformers, high-frequency antennas and short-wave high-frequency communication equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention relates to the technical field of soft magnetic ferrite materials, in particular to a nickel-zinc ferrite material as well as a preparation method and application thereof. The invention provides a nickel-zinc ferrite material. The nickel-zinc ferrite material comprises the following raw materials: main components and auxiliary components, wherein the main components comprise Fe2O3, NiO, ZnO and CuO; the mass percentage of Fe2O3 in the main component is 64.05 to 68.72 wt%, the mass percentage of NiO in the main component is 14.12 to 17.36 wt%, the mass percentage of ZnO in the main component is 11.61 to 15.02 wt%, and the mass percentage of CuO in the main component is 3.82 to 4.45 wt%; based on the total weight of the main components, the auxiliary components comprise 0.2 wt%-0.6 wt% of Al2O3, 0.05 wt%-0.25 wt% of SiO2 and 0.1 wt%-0.35 wt% of MnO2. According to the nickel-zinc ferrite material, specific main components and auxiliary components are selected, and the contents of the main components and the auxiliary components are limited, so that all the components generate a synergistic effect, and finally the nickel-zinc ferrite material with excellent comprehensive performance is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of soft ferrite materials, and in particular to a nickel-zinc ferrite material and a preparation method and application thereof. Background Art

[0002] Ferrite material is a new type of non-metallic magnetic material developed in the 1940s. It is generally divided into manganese zinc and nickel zinc materials. It is widely used in the module design of power supply and communication circuits, and is used as transformers, inductors, mutual inductors, filters, etc. With the development of microelectronics technology, the integration level continues to increase, and it continues to develop in the direction of high frequency, light weight, miniaturization, thinness, high reliability, high performance, and high speed. Soft magnetic materials are the main raw materials for the production of electronic components, and the performance requirements for soft magnetic materials are also getting higher and higher. Especially in the application of high-precision and reliable engineering technology, soft magnetic materials are required to have technical characteristics such as high frequency, high saturation flux density, and low loss.

[0003] Since nickel-zinc ferrite has high magnetic permeability, high resistivity, high frequency characteristics, and strong high-frequency interference suppression, it is widely used in various medium and high-frequency inductors, filters, transformers, high-frequency antennas, short-wave and high-frequency communications, etc. Especially in the increasingly powerful military fields such as aerospace, while meeting the requirements of high frequency, miniaturization, and lightweight, ferrite materials are required to have higher Curie temperature and lower loss.

[0004] Many well-known companies and institutions attach great importance to the development of high-frequency NiZn materials, such as Japan TDK's L18F material (magnetic permeability 200, Bs only 320, Curie temperature only 180 degrees); Hitachi Metals' DM-1 material (magnetic permeability 200, Bs only 230, Curie temperature is 200 degrees); ACME's H5R material (magnetic permeability 200, Bs is 400, Curie temperature is 200 degrees); Huayou's D3H material (magnetic permeability 200, Bs only There is 330, Curie temperature is 200 degrees); Fengyi's F8 material (magnetic permeability 200, Bs is 370, Curie temperature is 250 degrees); Tiantong's TN20H (magnetic permeability 200, Bs is 430, Curie temperature is 300 degrees). Although the Curie temperature is high, Bs still cannot meet the DC superposition requirements. For ferrite materials, it is easier to meet only one performance parameter of permeability, Bs or Curie temperature, but it is difficult to meet multiple characteristics at the same time.

[0005] Chinese patent application number 201110451252.2 discloses a high Ui and high Curie temperature magnesium zinc ferrite material and a preparation method. The main formula of the patent is: iron oxide Fe2O3 47.5-49.5 mol%, zinc oxide ZnO 23.5-28.2 mol%, magnesium oxide MgO 17-20.3 mol%, copper oxide CuO 4-8 mol%, and its magnetic permeability is 1800±25%, which cannot meet customers' performance inductance requirements such as high Bs and high Curie temperature.

[0006] The Chinese patent application number 201110314150.6 discloses a high-strength, heat-shock-resistant nickel core ferrite and its preparation method. The main components of the nickel core ferrite are calculated as oxides: Fe2O3 45-52mol%, NiO 20-39mol%, ZnO 20-30mol%, CuO 3-6.5mol%, and auxiliary components are SiO2 0.8-1.5wt%, CaCO3 0.2-0.5wt%, V2O5 0.05-0.19wt%, and Co2O3 0.01-0.09wt%. The magnetic permeability of the patent is 200±25%, which cannot meet the customer's performance inductance requirements such as high Bs and high Curie temperature.

[0007] Chinese patent literature discloses "a manganese-zinc ferrite material for anti-EMI and its preparation method", and its application publication number is CN105541316A. The invention has characteristics such as high Bs and high Tc, but its high-frequency performance is poor and cannot be used in high-frequency environments above 10MHz, and its surface resistance is low.

[0008] In summary, the main problem of nickel-zinc ferrite materials in related technologies is that it is difficult to have high magnetic permeability, Curie temperature, saturation magnetic induction intensity, and low high-frequency loss. Summary of the invention

[0009] Therefore, the technical problem to be solved by the present invention is to overcome the main problem of nickel-zinc ferrite materials in the related art, which is that it is difficult to have high magnetic permeability, Curie temperature, saturation magnetic induction intensity, and low high-frequency loss. Thus, a nickel-zinc ferrite material and a preparation method and application thereof are provided.

[0010] The present invention provides a nickel-zinc ferrite material, the raw materials of which include: a main component and a subsidiary component;

[0011] The main components include: Fe2O3, NiO, ZnO, CuO; the mass percentage of Fe2O3 in the main component is 64.05-68.72wt%, the mass percentage of NiO in the main component is 14.12-17.36wt%, the mass percentage of ZnO in the main component is 11.61-15.02wt%, and the mass percentage of CuO in the main component is 3.82-4.45wt%;

[0012] Based on the total weight of the main components, the auxiliary components include: Al2O3 0.2~0.6wt%, SiO2 0.05~0.25wt%, and MnO2 0.1~0.35wt%.

[0013] The present invention also provides a method for preparing the nickel-zinc ferrite material described above, comprising the following steps:

[0014] (1) grinding, mixing, drying and pre-calcining Fe2O3, NiO, ZnO, CuO and water to obtain a pre-calcined material;

[0015] (2) subjecting the pre-sintered material, Al2O3, SiO2, MnO2 and water to secondary sand milling, drying and dispersion to obtain a mixed pre-sintered material;

[0016] (3) mixing and granulating the mixed pre-sintered material, the binder and the defoamer to obtain an initial granular material;

[0017] (4) The initial granular material and the lubricant are mixed, pressed into shape, and sintered to obtain the nickel-zinc ferrite material.

[0018] Preferably, the sand milling and mixing process in step (1) is carried out in a sand mill;

[0019] Preferably, the sand milling mixing time in step (1) is 0.5-2h;

[0020] Preferably, in step (1), the mass ratio of the total weight of Fe2O3, NiO, ZnO and CuO, grinding balls and water in the sand milling mixture is (0.8-1.2): (4-5): (0.6-1);

[0021] Preferably, the pre-calcination temperature in step (1) is 800-1000° C. and the holding time is 3-7 hours.

[0022] Preferably, the pre-burning process in step (1) also includes a heating process; the heating process is to heat the dried material to the pre-burning temperature for 2-4 hours.

[0023] Preferably, the pre-firing process in step (1) also includes a cooling process.

[0024] Preferably, in step (2), the secondary sand milling mixing process is carried out in a sand mill;

[0025] Preferably, the sand milling mixing time in step (2) is 1 to 3 hours;

[0026] Preferably, the particle size of the material after sand grinding in step (2) is 0.4 to 1.3 μm;

[0027] Preferably, the mass ratio of the total weight of the pre-sintered material, Al2O3, SiO2 and MnO2, grinding balls and water is (0.8-1.2):(3.5-4.5):(0.8-1.2).

[0028] Preferably, in step (3), the mass ratio of the pre-sintered material, the adhesive and the defoaming agent is (85-100): (8-12): (0.01-0.1);

[0029] Preferably, the adhesive is selected from polyvinyl alcohol;

[0030] Preferably, the defoaming agent is selected from n-octanol.

[0031] Preferably, the granulation process is centrifugal spray granulation;

[0032] Preferably, the initial granules obtained by granulation have a particle size of 50-250 μm.

[0033] Preferably, in step (4), the mass ratio of the initial granular material to the lubricant is (80-120): (0.08-0.12);

[0034] Preferably, the lubricant is selected from zinc stearate.

[0035] Preferably, the compression molding pressure is 4-6 MPa.

[0036] Preferably, the density of the blank after pressing is 3.05-3.25 g / cm 3 .

[0037] Preferably, in step (4), the sintering temperature is 1040-1130° C., and the sintering time is 3-5 h;

[0038] Preferably, the atmosphere of the sintering process is air.

[0039] Preferably, in step (4), after the pressing and before the sintering, the process of heating at a heating rate of 2 to 5°C / min is also included;

[0040] Preferably, in step (4), after sintering, the process further includes cooling the temperature at a cooling rate of 3 to 5°C / min.

[0041] The present invention also provides an application of the nickel-zinc ferrite material described above or the nickel-zinc ferrite material prepared by the preparation method described above in high-frequency inductors, filters, transformers, high-frequency antennas, and short-wave high-frequency communication equipment.

[0042] The technical solution of the present invention has the following advantages:

[0043] The present invention provides a nickel-zinc ferrite material, wherein the raw materials include: a main component and a subsidiary component; wherein the main component includes: Fe2O3, NiO, ZnO, and CuO; the mass percentage of Fe2O3 in the main component is 64.05-68.72wt%, the mass percentage of NiO in the main component is 14.12-17.36wt%, the mass percentage of ZnO in the main component is 11.61-15.02wt%, and the mass percentage of CuO in the main component is 3.82-4.45wt%; based on the total weight of the main component, the subsidiary components include: Al2O3 0.2-0.6wt%, SiO2 0.05-0.25wt%, and MnO2 0.1-0.35wt%.

[0044] In the nickel-zinc ferrite material of the present invention, the addition of CuO can achieve the purpose of reducing the sintering temperature and improving the densification of the material, and can reduce the sintering temperature to below 1130°C and ensure good magnetic properties; MnO2 can improve the comprehensive performance of the material, especially reducing the coercive force and hysteresis loss, thereby reducing the total loss of the magnetic core, and also can improve the resistivity inside the grain; SiO2 can increase the stress insensitivity of the material, reduce the disadvantage of the low-temperature sintered NiCuZn ferrite being sensitive to compressive stress, and reduce the loss of the magnetic core; the addition of Al2O3 is beneficial to increasing the grain boundary thickness, inhibiting grain growth, By increasing the Curie temperature and saturation magnetic flux density, the Q value of the material can also be increased, thereby reducing the loss; by selecting specific main components and auxiliary components and limiting their respective contents, a synergistic effect is produced between the components, and finally a nickel-zinc ferrite material with excellent comprehensive performance is obtained (magnetic permeability 200±25%, Curie temperature greater than 300°C, Bs (4000A / m) greater than 485mT, relative loss factor tanδ / μi (×10^-6): <32 (f=1MHz)), which can be applied to high-frequency inductors, filters, transformers, high-frequency antennas, and short-wave high-frequency communication equipment with high-precision requirements. DETAILED DESCRIPTION

[0045] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.

[0046] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.

[0047] The molecular weight of the polyvinyl alcohol (PVA) used in the examples and comparative examples is 13,000-23,000.

[0048] Example 1

[0049] This embodiment provides a nickel-zinc ferrite material, and the preparation method includes the following steps:

[0050] (1) Weigh the main components of the raw materials: Fe2O3 66.4 g, NiO 16.35 g, ZnO 13.15 g, CuO 4.1 g, and the secondary components: SiO2 0.2 g, Al2O3 0.4 g, MnO2 0.3 g;

[0051] (2) mixing the main component of the raw material with water, and then mixing in a sand mill (wherein the mass ratio of the main component, grinding balls, and water is 1:4.5:0.8), crushing for 1.5 hours, and then drying, and then heating to 890±10°C for 4 hours, and then keeping the temperature at this temperature for 4 hours, and then cooling to obtain a pre-sintered material;

[0052] (3) grinding the pre-burned material and the SiO2, Al2O3, MnO2 and water weighed in step (1) in a sand mill for 2 h (the mass ratio of the total weight of the pre-burned material, Al2O3, SiO2 and MnO2, grinding balls and water is 1:4:1), and then drying, grinding and dispersing the obtained material (particle size of 0.5-1.2 μm (the particle size of the material is normally distributed)) to obtain a mixed pre-burned material;

[0053] (4) 100 g of the mixed pre-calcined material, 10 g of PVA, and 0.05 g of n-octanol are centrifugally sprayed through a spray tower to obtain an initial granular material with a particle size of 50-250 μm;

[0054] (5) The initial granules and zinc stearate were mixed in a mass ratio of 100:0.1 and then pressed into a powder with a density of 3.15 g / cm at a molding pressure of 5 MPa using a powder molding machine. 3 The green body is then heated to 1100°C at 3.0°C / min in an air atmosphere in a roller kiln, sintered for 4 hours, and then cooled at 3°C / min to obtain the nickel-zinc ferrite material.

[0055] Example 2

[0056] This embodiment provides a nickel-zinc ferrite material, and the preparation method includes the following steps:

[0057] (1) Weigh the main components of the raw materials: Fe2O3 64.3 g, NiO 17.31 g, ZnO 13.96 g, CuO 4.43 g, and the secondary components: SiO2 0.2 g, Al2O3 0.4 g, MnO2 0.3 g;

[0058] (2) mixing the main component of the raw material with water, and then mixing in a sand mill (wherein the mass ratio of the main component, grinding balls, and water is 1:4.5:0.8), crushing for 1.5 hours, and then drying, and then heating to 890±10°C for 4 hours, and then keeping the temperature at this temperature for 4 hours, and then cooling to obtain a pre-sintered material;

[0059] (3) grinding the pre-burned material and the SiO2, Al2O3, MnO2 and water weighed in step (1) in a sand mill (the mass ratio of the total weight of the pre-burned material, Al2O3, SiO2 and MnO2, grinding balls and water is 1:4:1), and then drying, grinding and dispersing the obtained material (particle size of 0.5-1.2 μm (the particle size of the material is normally distributed)) to obtain a mixed pre-burned material;

[0060] (4) 100 g of the mixed pre-calcined material, 10 g of PVA, and 0.05 g of n-octanol are centrifugally sprayed through a spray tower to obtain an initial granular material with a particle size of 50-250 μm;

[0061] (5) The initial granules and zinc stearate were mixed in a mass ratio of 100:0.1 and then pressed into a powder with a density of 3.15 g / cm at a molding pressure of 5 MPa using a powder molding machine. 3 The green body is then heated to 1100°C at 3.0°C / min in an air atmosphere in a roller kiln, sintered for 4 hours, and then cooled at 3°C / min to obtain the nickel-zinc ferrite material.

[0062] Example 3

[0063] This embodiment provides a nickel-zinc ferrite material, and the preparation method includes the following steps:

[0064] (1) Weigh the main components of the raw materials: Fe2O3 68.66 g, NiO 14.46 g, ZnO 11.86 g, CuO 4.02 g, and the secondary components: SiO2 0.2 g, Al2O3 0.5 g, MnO2 0.35 g;

[0065] (2) mixing the main component of the raw material with water, and then mixing in a sand mill (wherein the mass ratio of the main component, grinding balls, and water is 1:4.5:0.8), crushing for 1.5 hours, and then drying, and then heating to 890±10°C for 4 hours, and then keeping the temperature at this temperature for 4 hours, and then cooling to obtain a pre-sintered material;

[0066] (3) grinding the pre-burned material and the SiO2, Al2O3, MnO2 and water weighed in step (1) in a sand mill (the mass ratio of the total weight of the pre-burned material, Al2O3, SiO2 and MnO2, grinding balls and water is 1:4:1), and then drying, grinding and dispersing the obtained material (particle size of 0.5-1.2 μm (the particle size of the material is normally distributed)) to obtain a mixed pre-burned material;

[0067] (4) 100 g of the mixed pre-calcined material, 10 g of PVA, and 0.05 g of n-octanol are centrifugally sprayed through a spray tower to obtain an initial granular material with a particle size of 50-250 μm;

[0068] (5) The initial granules and zinc stearate were mixed in a mass ratio of 100:0.1 and then pressed into a powder with a density of 3.15 g / cm at a molding pressure of 5 MPa using a powder molding machine. 3 The green body is then heated to 1100°C at 3.0°C / min in an air atmosphere in a roller kiln, sintered for 4 hours, and then cooled at 3°C / min to obtain the nickel-zinc ferrite material.

[0069] Example 4

[0070] This embodiment provides a nickel-zinc ferrite material, and the preparation method includes the following steps:

[0071] (1) Weigh the main components of the raw materials: Fe2O3 66.9 g, NiO 15.5 g, ZnO 13.5 g, CuO 4.1 g, and the secondary components: SiO2 0.2 g, Al2O3 0.4 g, MnO2 0.3 g;

[0072] (2) mixing the main component of the raw material with water, and then mixing in a sand mill (wherein the mass ratio of the main component, grinding balls, and water is 1:4.5:0.8), crushing for 1.5 hours, and then drying, and then heating to 890±10°C for 4 hours, and then keeping the temperature at this temperature for 4 hours, and then cooling to obtain a pre-sintered material;

[0073] (3) grinding the pre-burned material and the SiO2, Al2O3, MnO2 and water weighed in step (1) in a sand mill (the mass ratio of the total weight of the pre-burned material, Al2O3, SiO2 and MnO2, grinding balls and water is 1:4:1), and then drying, grinding and dispersing the obtained material (particle size of 0.5-1.2 μm (the particle size of the material is normally distributed)) to obtain a mixed pre-burned material;

[0074] (4) 100 g of the mixed pre-calcined material, 10 g of PVA, and 0.05 g of n-octanol are centrifugally sprayed through a spray tower to obtain an initial granular material with a particle size of 50-250 μm;

[0075] (5) The initial granules and zinc stearate were mixed in a mass ratio of 100:0.1 and then pressed into a powder with a density of 3.15 g / cm at a molding pressure of 5 MPa using a powder molding machine. 3 The green body is then heated to 1100°C at 3.0°C / min in an air atmosphere in a roller kiln, sintered for 4 hours, and then cooled at 3°C / min to obtain the nickel-zinc ferrite material.

[0076] Example 5

[0077] This embodiment provides a nickel-zinc ferrite material, and the preparation method includes the following steps:

[0078] (1) Weigh the main components of the raw materials: Fe2O3 67.15 g, NiO 15.37 g, ZnO 13.38 g, CuO 4.1 g, and the secondary components: SiO2 0.2 g, Al2O3 0.4 g, MnO2 0.3 g;

[0079] (2) mixing the main component of the raw material with water, and then mixing in a sand mill (wherein the mass ratio of the main component, grinding balls, and water is 1:4.5:0.8), crushing for 1.5 hours, and then drying, and then heating to 890±10°C for 4 hours, and then keeping the temperature at this temperature for 4 hours, and then cooling to obtain a pre-sintered material;

[0080] (3) grinding the pre-burned material and the SiO2, Al2O3, MnO2 and water weighed in step (1) in a sand mill (the mass ratio of the total weight of the pre-burned material, Al2O3, SiO2 and MnO2, grinding balls and water is 1:4:1), and then drying, grinding and dispersing the obtained material (particle size of 0.5-1.2 μm (the particle size of the material is normally distributed)) to obtain a mixed pre-burned material;

[0081] (4) 100 g of the mixed pre-calcined material, 10 g of PVA, and 0.05 g of n-octanol are centrifugally sprayed through a spray tower to obtain an initial granular material with a particle size of 50-250 μm;

[0082] (5) The initial granules and zinc stearate were mixed in a mass ratio of 100:0.1 and then pressed into a powder with a density of 3.15 g / cm at a molding pressure of 5 MPa using a powder molding machine. 3 The green body is then heated to 1100°C at 3.0°C / min in an air atmosphere in a roller kiln, sintered for 4 hours, and then cooled at 3°C / min to obtain the nickel-zinc ferrite material.

[0083] Example 6

[0084] This embodiment provides a nickel-zinc ferrite material, and the preparation method includes the following steps:

[0085] (1) Weigh the main components of the raw materials: Fe2O3 66.28 g, NiO 16.78 g, ZnO 12.84 g, CuO 4.1 g, and weigh the secondary components: SiO2 0.2 g, Al2O3 0.4 g, MnO2 0.3 g;

[0086] (2) mixing the main component of the raw material with water, and then mixing in a sand mill (wherein the mass ratio of the main component, grinding balls, and water is 1:4.5:0.8), crushing for 1.5 hours, and then drying, and then heating to 890±10°C for 4 hours, and then keeping the temperature at this temperature for 4 hours, and then cooling to obtain a pre-sintered material;

[0087] (3) grinding the pre-burned material and the SiO2, Al2O3, MnO2 and water weighed in step (1) in a sand mill (the mass ratio of the total weight of the pre-burned material, Al2O3, SiO2 and MnO2, grinding balls and water is 1:4:1), and then drying, grinding and dispersing the obtained material (particle size of 0.5-1.2 μm (the particle size of the material is normally distributed)) to obtain a mixed pre-burned material;

[0088] (4) 100 g of the mixed pre-calcined material, 10 g of PVA, and 0.05 g of n-octanol are centrifugally sprayed through a spray tower to obtain an initial granular material with a particle size of 50-250 μm;

[0089] (5) The initial granules and zinc stearate were mixed in a mass ratio of 100:0.1 and then pressed into a powder with a density of 3.15 g / cm at a molding pressure of 5 MPa using a powder molding machine. 3 The green body is then heated to 1100°C at 3.0°C / min in an air atmosphere in a roller kiln, sintered for 4 hours, and then cooled at 3°C / min to obtain the nickel-zinc ferrite material.

[0090] Example 7

[0091] This embodiment provides a nickel-zinc ferrite material, and the preparation method includes the following steps:

[0092] (1) Weigh the main components of the raw materials: Fe2O3 65.75 g, NiO 16.59 g, ZnO 13.46 g, CuO 4.2 g, and the secondary components: SiO2 0.2 g, Al2O3 0.4 g, MnO2 0.25 g;

[0093] (2) mixing the main component of the raw material with water, and then mixing in a sand mill (wherein the mass ratio of the main component, grinding balls, and water is 1:4.5:0.8), crushing for 1.5 hours, and then drying, and then heating to 890±10°C for 4 hours, and then keeping the temperature at this temperature for 4 hours, and then cooling to obtain a pre-sintered material;

[0094] (3) grinding the pre-burned material and the SiO2, Al2O3, MnO2 and water weighed in step (1) in a sand mill (the mass ratio of the total weight of the pre-burned material, Al2O3, SiO2 and MnO2, grinding balls and water is 1:4:1), and then drying, grinding and dispersing the obtained material (particle size of 0.5-1.2 μm (the particle size of the material is normally distributed)) to obtain a mixed pre-burned material;

[0095] (4) 100 g of the mixed pre-calcined material, 10 g of PVA, and 0.05 g of n-octanol are centrifugally sprayed through a spray tower to obtain an initial granular material with a particle size of 50-250 μm;

[0096] (5) The initial granules and zinc stearate were mixed in a mass ratio of 100:0.1 and then pressed into a powder with a density of 3.15 g / cm at a molding pressure of 5 MPa using a powder molding machine. 3 The green body is then heated to 1100°C at 3.0°C / min in an air atmosphere in a roller kiln, sintered for 4 hours, and then cooled at 3°C / min to obtain the nickel-zinc ferrite material.

[0097] Example 8

[0098] This embodiment provides a nickel-zinc ferrite material, and the preparation method includes the following steps:

[0099] (1) Weigh the main components of the raw materials: Fe2O3 65.55 g, NiO 16.15 g, ZnO 14.2 g, CuO 4.1 g, and the auxiliary components: SiO2 0.2 g, Al2O3 0.3 g, MnO2 0.3 g;

[0100] (2) mixing the main component of the raw material with water, and then mixing in a sand mill (wherein the mass ratio of the main component, grinding balls, and water is 1:4.5:0.8), crushing for 1.5 hours, and then drying, and then heating to 890±10°C for 4 hours, and then keeping the temperature at this temperature for 4 hours, and then cooling to obtain a pre-sintered material;

[0101] (3) grinding the pre-burned material and the SiO2, Al2O3, MnO2 and water weighed in step (1) in a sand mill (the mass ratio of the total weight of the pre-burned material, Al2O3, SiO2 and MnO2, grinding balls and water is 1:4:1), and then drying, grinding and dispersing the obtained material (particle size of 0.5-1.2 μm (the particle size of the material is normally distributed)) to obtain a mixed pre-burned material;

[0102] (4) 100 g of the mixed pre-calcined material, 10 g of PVA, and 0.05 g of n-octanol are centrifugally sprayed through a spray tower to obtain an initial granular material with a particle size of 50-250 μm;

[0103] (5) The initial granules and zinc stearate were mixed in a mass ratio of 100:0.1 and then pressed into a powder with a density of 3.15 g / cm at a molding pressure of 5 MPa using a powder molding machine. 3 The green body is then heated to 1100°C at 3.0°C / min in an air atmosphere in a roller kiln, sintered for 4 hours, and then cooled at 3°C / min to obtain the nickel-zinc ferrite material.

[0104] Comparative Example 1

[0105] This comparative example provides a nickel-zinc ferrite material, and the preparation method comprises the following steps:

[0106] (1) Weigh the main components of the raw materials: Fe2O3 66.6 g, NiO 17.84 g, ZnO 11.51 g, CuO 4.05 g, and the auxiliary components: SiO2 0.1 g, Al2O3 0.5 g, MnO2 0.3 g;

[0107] (2) mixing the main component of the raw material with water, and then mixing in a sand mill (wherein the mass ratio of the main component, grinding balls, and water is 1:4.5:0.8), crushing for 1.5 hours, and then drying, and then heating to 890±10°C for 4 hours, and then keeping the temperature at this temperature for 4 hours, and then cooling to obtain a pre-sintered material;

[0108] (3) grinding the pre-burned material and the SiO2, Al2O3, MnO2 and water weighed in step (1) in a sand mill (the mass ratio of the total weight of the pre-burned material, Al2O3, SiO2 and MnO2, grinding balls and water is 1:4:1), and then drying, grinding and dispersing the obtained material (particle size of 0.5-1.2 μm (the particle size of the material is normally distributed)) to obtain a mixed pre-burned material;

[0109] (4) 100 g of the mixed pre-calcined material, 10 g of PVA, and 0.05 g of n-octanol are centrifugally sprayed through a spray tower to obtain an initial granular material with a particle size of 50-250 μm;

[0110] (5) The initial granules and zinc stearate were mixed in a mass ratio of 100:0.1 and then pressed into a powder with a density of 3.15 g / cm at a molding pressure of 5 MPa using a powder molding machine. 3 The green body is then heated to 1100°C at 3.0°C / min in an air atmosphere in a roller kiln, sintered for 4 hours, and then cooled at 3°C / min to obtain the nickel-zinc ferrite material.

[0111] Comparative Example 2

[0112] This comparative example provides a nickel-zinc ferrite material, and the preparation method comprises the following steps:

[0113] (1) Weigh the main components of the raw materials: Fe2O3 68.96 g, NiO 14.75 g, ZnO 12.55 g, CuO 3.86 g, and the secondary components: SiO2 0.2 g, Al2O3 0.4 g, MnO2 0.3 g;

[0114] (2) mixing the main component of the raw material with water, and then mixing in a sand mill (wherein the mass ratio of the main component, grinding balls, and water is 1:4.5:0.8), crushing for 1.5 hours, and then drying, and then heating to 890±10°C for 4 hours, and then keeping the temperature at this temperature for 4 hours, and then cooling to obtain a pre-sintered material;

[0115] (3) grinding the pre-burned material and the SiO2, Al2O3, MnO2 and water weighed in step (1) in a sand mill (the mass ratio of the total weight of the pre-burned material, Al2O3, SiO2 and MnO2, grinding balls and water is 1:4:1), and then drying, grinding and dispersing the obtained material (particle size of 0.5-1.2 μm (the particle size of the material is normally distributed)) to obtain a mixed pre-burned material;

[0116] (4) 100 g of the mixed pre-calcined material, 10 g of PVA, and 0.05 g of n-octanol are centrifugally sprayed through a spray tower to obtain an initial granular material with a particle size of 50-250 μm;

[0117] (5) The initial granules and zinc stearate were mixed in a mass ratio of 100:0.1 and then pressed into a powder with a density of 3.15 g / cm at a molding pressure of 5 MPa using a powder molding machine. 3 The green body is then heated to 1100°C at 3.0°C / min in an air atmosphere in a roller kiln, sintered for 4 hours, and then cooled at 3°C / min to obtain the nickel-zinc ferrite material.

[0118] Comparative Example 3

[0119] This comparative example provides a nickel-zinc ferrite material, and the preparation method comprises the following steps:

[0120] (1) Weigh the main components of the raw materials: Fe2O3 66.2g, NiO 16.35g, ZnO 12.95g, CuO 4.5g, and the secondary components: SiO2 0.25g, Al2O3 0.3g, MnO2 0.05g;

[0121] (2) mixing the main component of the raw material with water, and then mixing in a sand mill (wherein the mass ratio of the main component, grinding balls, and water is 1:4.5:0.8), crushing for 1.5 hours, and then drying, and then heating to 890±10°C for 4 hours, and then keeping the temperature at this temperature for 4 hours, and then cooling to obtain a pre-sintered material;

[0122] (3) grinding the pre-burned material and the SiO2, Al2O3, MnO2 and water weighed in step (1) in a sand mill (the mass ratio of the total weight of the pre-burned material, Al2O3, SiO2 and MnO2, grinding balls and water is 1:4:1), and then drying, grinding and dispersing the obtained material (particle size of 0.5-1.2 μm (the particle size of the material is normally distributed)) to obtain a mixed pre-burned material;

[0123] (4) 100 g of the mixed pre-calcined material, 10 g of PVA, and 0.05 g of n-octanol are centrifugally sprayed through a spray tower to obtain an initial granular material with a particle size of 50-250 μm;

[0124] (5) The initial granules and zinc stearate were mixed in a mass ratio of 100:0.1 and then pressed into a powder with a density of 3.15 g / cm at a molding pressure of 5 MPa using a powder molding machine. 3 The green body is then heated to 1100°C at 3.0°C / min in an air atmosphere in a roller kiln, sintered for 4 hours, and then cooled at 3°C / min to obtain the nickel-zinc ferrite material.

[0125] Comparative Example 4

[0126] This comparative example provides a nickel-zinc ferrite material, and the preparation method comprises the following steps:

[0127] (1) Weigh the main components of the raw materials: Fe2O3 66.4 g, NiO 14.05 g, ZnO 15.45 g, CuO 4.1 g, and the secondary components: SiO2 0.2 g, Al2O3 0.25 g, MnO2 0.3 g;

[0128] (2) mixing the main component of the raw material with water, and then mixing in a sand mill (wherein the mass ratio of the main component, grinding balls, and water is 1:4.5:0.8), crushing for 1.5 hours, and then drying, and then heating to 890±10°C for 4 hours, and then keeping the temperature at this temperature for 4 hours, and then cooling to obtain a pre-sintered material;

[0129] (3) grinding the pre-burned material and the SiO2, Al2O3, MnO2 and water weighed in step (1) in a sand mill (the mass ratio of the total weight of the pre-burned material, Al2O3, SiO2 and MnO2, grinding balls and water is 1:4:1), and then drying, grinding and dispersing the obtained material (particle size of 0.5-1.2 μm (the particle size of the material is normally distributed)) to obtain a mixed pre-burned material;

[0130] (4) 100 g of the mixed pre-calcined material, 10 g of PVA, and 0.05 g of n-octanol are centrifugally sprayed through a spray tower to obtain an initial granular material with a particle size of 50-250 μm;

[0131] (5) The initial granules and zinc stearate were mixed in a mass ratio of 100:0.1 and then pressed into a powder with a density of 3.15 g / cm at a molding pressure of 5 MPa using a powder molding machine. 3 The green body is then heated to 1100°C at 3.0°C / min in an air atmosphere in a roller kiln, sintered for 4 hours, and then cooled at 3°C / min to obtain the nickel-zinc ferrite material.

[0132] Comparative Example 5

[0133] This comparative example provides a nickel-zinc ferrite material, and the preparation method comprises the following steps:

[0134] (1) Weigh the main components of the raw materials: Fe2O3 63.96 g, NiO 16.35 g, ZnO 15.59 g, CuO 4.1 g, and the secondary components: SiO2 0.2 g, Al2O3 0.2 g, MnO2 0.3 g;

[0135] (2) mixing the main component of the raw material with water, and then mixing in a sand mill (wherein the mass ratio of the main component, grinding balls, and water is 1:4.5:0.8), crushing for 1.5 hours, and then drying, and then heating to 890±10°C for 4 hours, and then keeping the temperature at this temperature for 4 hours, and then cooling to obtain a pre-sintered material;

[0136] (3) grinding the pre-burned material and the SiO2, Al2O3, MnO2 and water weighed in step (1) in a sand mill (the mass ratio of the total weight of the pre-burned material, Al2O3, SiO2 and MnO2, grinding balls and water is 1:4:1), and then drying, grinding and dispersing the obtained material (particle size of 0.5-1.2 μm (the particle size of the material is normally distributed)) to obtain a mixed pre-burned material;

[0137] (4) 100 g of the mixed pre-calcined material, 10 g of PVA, and 0.05 g of n-octanol are centrifugally sprayed through a spray tower to obtain an initial granular material with a particle size of 50-250 μm;

[0138] (5) The initial granules and zinc stearate were mixed in a mass ratio of 100:0.1 and then pressed into a powder with a density of 3.15 g / cm at a molding pressure of 5 MPa using a powder molding machine. 3 The green body is then heated to 1100°C at 3.0°C / min in an air atmosphere in a roller kiln, sintered for 4 hours, and then cooled at 3°C / min to obtain the nickel-zinc ferrite material.

[0139] Comparative Example 6

[0140] This comparative example provides a nickel-zinc ferrite material, and the preparation method comprises the following steps:

[0141] (1) Weigh the main components of the raw materials: Fe2O3 66.4 g, NiO 16.35 g, ZnO 13.15 g, CuO 4.1 g, and the secondary components: SiO2 0.2 g, Al2O3 0.1 g, MnO2 1.05 g;

[0142] (2) mixing the main component of the raw material with water, and then mixing in a sand mill (wherein the mass ratio of the main component, grinding balls, and water is 1:4.5:0.8), crushing for 1.5 hours, and then drying, and then heating to 890±10°C for 4 hours, and then keeping the temperature at this temperature for 4 hours, and then cooling to obtain a pre-sintered material;

[0143] (3) grinding the pre-burned material and the SiO2, Al2O3, MnO2 and water weighed in step (1) in a sand mill (the mass ratio of the total weight of the pre-burned material, Al2O3, SiO2 and MnO2, grinding balls and water is 1:4:1), and then drying, grinding and dispersing the obtained material (particle size of 0.5-1.2 μm (the particle size of the material is normally distributed)) to obtain a mixed pre-burned material;

[0144] (4) 100 g of the mixed pre-calcined material, 10 g of PVA, and 0.05 g of n-octanol are centrifugally sprayed through a spray tower to obtain an initial granular material with a particle size of 50-250 μm;

[0145] (5) The initial granules and zinc stearate were mixed in a mass ratio of 100:0.1 and then pressed into a powder with a density of 3.15 g / cm at a molding pressure of 5 MPa using a powder molding machine. 3 The green body is then heated to 1100°C at 3.0°C / min in an air atmosphere in a roller kiln, sintered for 4 hours, and then cooled at 3°C / min to obtain the nickel-zinc ferrite material.

[0146] Comparative Example 7

[0147] This comparative example provides a nickel-zinc ferrite material, and the preparation method comprises the following steps:

[0148] (1) Weigh the main components of the raw materials: Fe2O3 65.55 g, NiO 16.15 g, ZnO 14.2 g, CuO 4.1 g, and the secondary components: SiO2 0.2 g, Al2O3 0.1 g, MnO2 0.4 g;

[0149] (2) mixing the main component of the raw material with water, and then mixing in a sand mill (wherein the mass ratio of the main component, grinding balls, and water is 1:4.5:0.8), crushing for 1.5 hours, and then drying, and then heating to 890±10°C for 4 hours, and then keeping the temperature at this temperature for 4 hours, and then cooling to obtain a pre-sintered material;

[0150] (3) grinding the pre-burned material and the SiO2, Al2O3, MnO2 and water weighed in step (1) in a sand mill (the mass ratio of the total weight of the pre-burned material, Al2O3, SiO2 and MnO2, grinding balls and water is 1:4:1), and then drying, grinding and dispersing the obtained material (particle size of 0.5-1.2 μm (the particle size of the material is normally distributed)) to obtain a mixed pre-burned material;

[0151] (4) 100 g of the mixed pre-calcined material, 10 g of PVA, and 0.05 g of n-octanol are centrifugally sprayed through a spray tower to obtain an initial granular material with a particle size of 50-250 μm;

[0152] (5) The initial granules and zinc stearate were mixed in a mass ratio of 100:0.1 and then pressed into a powder with a density of 3.15 g / cm at a molding pressure of 5 MPa using a powder molding machine. 3 The green body is then heated to 1100°C at 3.0°C / min in an air atmosphere in a roller kiln, sintered for 4 hours, and then cooled at 3°C / min to obtain the nickel-zinc ferrite material.

[0153] Comparative Example 8

[0154] This comparative example provides a nickel-zinc ferrite material, and the preparation method comprises the following steps:

[0155] (1) Weigh the main components of the raw materials: Fe2O3 66.4 g, NiO 16.35 g, ZnO 13.15 g, CuO 4.1 g, and the secondary components: Al2O3 0.51 g, MnO2 0.39 g;

[0156] (2) mixing the main component of the raw material with water, and then mixing in a sand mill (wherein the mass ratio of the main component, grinding balls, and water is 1:4.5:0.8), crushing for 1.5 hours, and then drying, and then heating to 890±10°C for 4 hours, and then keeping the temperature at this temperature for 4 hours, and then cooling to obtain a pre-sintered material;

[0157] (3) grinding the pre-burned material and the Al2O3, MnO2 and water weighed in step (1) in a sand mill (the mass ratio of the total weight of the pre-burned material, Al2O3 and MnO2, grinding balls and water is 1:4:1), and then drying, grinding and dispersing the obtained material (particle size of 0.5-1.2 μm (the particle size of the material is normally distributed)) to obtain a mixed pre-burned material;

[0158] (4) 100 g of the mixed pre-calcined material, 10 g of PVA, and 0.05 g of n-octanol are centrifugally sprayed through a spray tower to obtain an initial granular material with a particle size of 50-250 μm;

[0159] (5) The initial granules and zinc stearate were mixed in a mass ratio of 100:0.1 and then pressed into a powder with a density of 3.15 g / cm at a molding pressure of 5 MPa using a powder molding machine. 3 The green body is then heated to 1100°C at 3.0°C / min in an air atmosphere in a roller kiln, sintered for 4 hours, and then cooled at 3°C / min to obtain the nickel-zinc ferrite material.

[0160] Comparative Example 9

[0161] This comparative example provides a nickel-zinc ferrite material, and the preparation method comprises the following steps:

[0162] (1) Weigh the main components of the raw materials: Fe2O3 66.4 g, NiO 16.35 g, ZnO 13.15 g, CuO 4.1 g, and the secondary components: SiO2 0.36 g, MnO2 0.54 g;

[0163] (2) mixing the main component of the raw material with water, and then mixing in a sand mill (wherein the mass ratio of the main component, grinding balls, and water is 1:4.5:0.8), crushing for 1.5 hours, and then drying, and then heating to 890±10°C for 4 hours, and then keeping the temperature at this temperature for 4 hours, and then cooling to obtain a pre-sintered material;

[0164] (3) grinding the pre-burned material and the SiO2, MnO2 and water weighed in step (1) in a sand mill (the mass ratio of the total weight of the pre-burned material, SiO2 and MnO2, grinding balls and water is 1:4:1), and then drying, grinding and dispersing the obtained material (particle size of 0.5-1.2 μm (the particle size of the material is normally distributed)) to obtain a mixed pre-burned material;

[0165] (4) 100 g of the mixed pre-calcined material, 10 g of PVA, and 0.05 g of n-octanol are centrifugally sprayed through a spray tower to obtain an initial granular material with a particle size of 50-250 μm;

[0166] (5) The initial granules and zinc stearate were mixed in a mass ratio of 100:0.1 and then pressed into a powder with a density of 3.15 g / cm at a molding pressure of 5 MPa using a powder molding machine. 3 The green body is then heated to 1100°C at 3.0°C / min in an air atmosphere in a roller kiln, sintered for 4 hours, and then cooled at 3°C / min to obtain the nickel-zinc ferrite material.

[0167] Comparative Example 10

[0168] This comparative example provides a nickel-zinc ferrite material, and the preparation method comprises the following steps:

[0169] (1) Weigh the main components of the raw materials: Fe2O3 66.4 g, NiO 16.35 g, ZnO 13.15 g, CuO 4.1 g, and the secondary components: SiO2 0.3 g, Al2O3 0.5 g;

[0170] (2) mixing the main component of the raw material with water, and then mixing in a sand mill (wherein the mass ratio of the main component, grinding balls, and water is 1:4.5:0.8), crushing for 1.5 hours, and then drying, and then heating to 890±10°C for 4 hours, and then keeping the temperature at this temperature for 4 hours, and then cooling to obtain a pre-sintered material;

[0171] (3) grinding the pre-burned material and the SiO2, Al2O3 and water weighed in step (1) in a sand mill (the mass ratio of the total weight of the pre-burned material, Al2O3 and SiO2, grinding balls and water is 1:4:1), and then drying, grinding and dispersing the obtained material (particle size of 0.5-1.2 μm (the particle size of the material is normally distributed)) to obtain a mixed pre-burned material;

[0172] (4) 100 g of the mixed pre-calcined material, 10 g of PVA, and 0.05 g of n-octanol are centrifugally sprayed through a spray tower to obtain an initial granular material with a particle size of 50-250 μm;

[0173] (5) The initial granules and zinc stearate were mixed in a mass ratio of 100:0.1 and then pressed into a powder with a density of 3.15 g / cm at a molding pressure of 5 MPa using a powder molding machine. 3 The green body is then heated to 1100°C at 3.0°C / min in an air atmosphere in a roller kiln, sintered for 4 hours, and then cooled at 3°C / min to obtain the nickel-zinc ferrite material.

[0174] Comparative Example 11

[0175] This comparative example provides a nickel-zinc ferrite material, and the preparation method comprises the following steps:

[0176] (1) Weigh the main components of raw materials: Fe2O3 66.4 g, NiO 16.35 g, ZnO 13.15 g, CuO 4.1 g;

[0177] (2) mixing the main component of the raw material with water, and then mixing in a sand mill (wherein the mass ratio of the main component, grinding balls, and water is 1:4.5:0.8), crushing for 1.5 hours, and then drying, and then heating to 890±10°C for 4 hours, and then keeping the temperature at this temperature for 4 hours, and then cooling to obtain a pre-sintered material;

[0178] (3) grinding the pre-burned material and water in a sand mill (the mass ratio of the pre-burned material weight, grinding balls, and water is 1:4:1), drying, grinding, and dispersing the obtained material (particle size of 0.5-1.2 μm (the particle size of the material is normally distributed)) to obtain a mixed pre-burned material;

[0179] (4) 100 g of the mixed pre-calcined material, 10 g of PVA, and 0.05 g of n-octanol are centrifugally sprayed through a spray tower to obtain an initial granular material with a particle size of 50-250 μm;

[0180] (5) The initial granules and zinc stearate were mixed in a mass ratio of 100:0.1 and then pressed into a powder with a density of 3.15 g / cm at a molding pressure of 5 MPa using a powder molding machine. 3The green body is then heated to 1100°C at 3.0°C / min in an air atmosphere in a roller kiln, sintered for 4 hours, and then cooled at 3°C / min to obtain the nickel-zinc ferrite material.

[0181] Test Case

[0182] The nickel-zinc ferrite material prepared in the embodiment and the comparative example was prepared into a sample ring with an outer diameter of 25 mm, an inner diameter of 15 mm, and a height of 7 mm, and the inductance and Q value were tested using an Aglient E4980A tester. Test conditions: Φ0.35 mm enameled wire, 20 turns, T = 25 ° C, u = 0.25 v, F = 1 KHz ~ 2 MHz;

[0183] Use Aglient E4980A and a high and low temperature controlled oven to test the Curie temperature Tc and the inductance at each temperature, and then calculate μi and relative loss factor based on the inductance and Q value data;

[0184] The magnetic flux density Bs was tested using the SY8232 instrument produced by Iwasaki Corporation of Japan;

[0185] The surface resistance was tested with SM-8220 test instrument, and the insulation resistance R at both ends of Ф10*2mm was tested with Agilent4339B high resistance meter, and the resistivity ρ was calculated.

[0186] Magnetic permeability is a measure of the magnetization intensity of a material in response to an applied magnetic field. It is represented by μi in the electronics industry. Magnetic permeability represents the inductance per unit length and is calculated by measuring the inductance of the magnetic core.

[0187]

[0188] Where, L: coil inductance with magnetic core (H); Lo: coil inductance without magnetic core (H); N: number of coil turns; Ae: effective cross-sectional area of ​​magnetic core (cm 2 ); Le: effective magnetic path length of the core (cm).

[0189] The relative loss factor (tanδ / μi) is the ratio of the loss factor to the magnetic permeability. The lower the value, the smaller the loss of the material and the higher the electromagnetic performance. It is calculated according to the following formula:

[0190] tanδ / μi=1 / (Q×μi)

[0191] tanδ is the core loss, which is the reciprocal of the quality factor Q (tanδ=1 / Q)

[0192] μi is the magnetic permeability;

[0193] The test or calculation results are shown in Table 1:

[0194] Table 1

[0195]

[0196]

[0197] Obviously, the above embodiments are merely examples for clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the protection scope of the invention.

Claims

1. A nickel-zinc ferrite material, characterized in that: Raw materials include: main ingredients, auxiliary ingredients; The main components include: Fe2O3, NiO, ZnO, CuO; the mass percentage of Fe2O3 in the main component is 64.05-68.72wt%, the mass percentage of NiO in the main component is 14.12-17.36wt%, the mass percentage of ZnO in the main component is 11.61-15.02wt%, and the mass percentage of CuO in the main component is 3.82-4.45wt%; Based on the total weight of the main components, the auxiliary components include: Al2O3 0.2~0.6wt%, SiO2 0.05~0.25wt%, and MnO2 0.1~0.35wt%.

2. A method for preparing the nickel-zinc ferrite material according to claim 1, characterized in that: The steps include: (1) grinding, mixing, drying and pre-calcining Fe2O3, NiO, ZnO, CuO and water to obtain a pre-calcined material; (2) subjecting the pre-sintered material, Al2O3, SiO2, MnO2 and water to secondary sand milling, drying and dispersion to obtain a mixed pre-sintered material; (3) mixing and granulating the mixed pre-sintered material, the binder and the defoamer to obtain an initial granular material; (4) The initial granular material and the lubricant are mixed, pressed into shape, and sintered to obtain the nickel-zinc ferrite material.

3. The method for preparing the nickel-zinc ferrite material according to claim 2, characterized in that: The primary sand milling and mixing process in step (1) is carried out in a sand mill; Preferably, the sand milling mixing time in step (1) is 0.5-2h; Preferably, in step (1), the mass ratio of the total weight of Fe2O3, NiO, ZnO and CuO, grinding balls and water in the sand milling mixture is (0.8-1.2): (4-5): (0.6-1); Preferably, the pre-sintering temperature in step (1) is 800-1000° C. and the holding time is 3-7 hours.

4. The method for preparing the nickel-zinc ferrite material according to claim 2 or 3, characterized in that: In step (2), the secondary sand milling mixing process is carried out in a sand mill; Preferably, the sand milling mixing time in step (2) is 1 to 3 hours; Preferably, the particle size of the material after sand grinding in step (2) is 0.4 to 1.3 μm; Preferably, the mass ratio of the total weight of the pre-sintered material, Al2O3, SiO2 and MnO2, grinding balls and water is (0.8-1.2):(3.5-4.5):(0.8-1.2).

5. The method for preparing the nickel-zinc ferrite material according to any one of claims 2 to 4, characterized in that: In step (3), the mass ratio of the pre-sintered material, the adhesive and the defoaming agent is (85-100): (8-12): (0.01-0.1); Preferably, the adhesive is selected from polyvinyl alcohol; Preferably, the defoaming agent is selected from n-octanol.

6. The method for preparing the nickel-zinc ferrite material according to any one of claims 2 to 5, characterized in that: The granulation process is centrifugal spray granulation; Preferably, the initial granules obtained by granulation have a particle size of 50-250 μm.

7. The method for preparing the nickel-zinc ferrite material according to any one of claims 2 to 6, characterized in that: In step (4), the mass ratio of the initial granular material to the lubricant is (80-120): (0.08-0.12); Preferably, the lubricant is selected from zinc stearate; Preferably, the density of the blank after pressing is 3.05-3.25 g / cm 3 .

8. The method for preparing the nickel-zinc ferrite material according to any one of claims 2 to 7, characterized in that: In step (4), the sintering temperature is 1040-1130° C. and the sintering time is 3-5 hours; Preferably, the atmosphere of the sintering process is air.

9. The method for preparing the nickel-zinc ferrite material according to any one of claims 2 to 8, characterized in that: In step (4), after the pressing and before the sintering, the process of heating the material at a heating rate of 2 to 5°C / min is also included; Preferably, in step (4), after sintering, the process further includes cooling the temperature at a cooling rate of 3 to 5°C / min.

10. Use of the nickel-zinc ferrite material according to claim 1 or the nickel-zinc ferrite material prepared by the preparation method according to any one of claims 2 to 9 in high-frequency inductors, filters, transformers, high-frequency antennas, and short-wave high-frequency communication equipment.

Citation Information

Patent Citations

  • High-strength thermal-shock-resistant nickel zinc ferrite and preparation method thereof

    CN102432279A

  • High-initial-permeability (mu i) and high-Curie-temperature magnesium-zinc ferrite material and preparation method thereof

    CN102557602A

  • Manganese zinc ferrite material for resisting EMI and preparation method thereof

    CN105541316A

  • Nickel-copper-zinc ferrite material with high surface resistance for panel display

    CN102329129A

  • High-strength high-Bs (saturation magnetic induction intensity) nickel-zinc ferrite and preparation method thereof

    CN102603279A

Cited By

  • Nickel-zinc ferrite material as well as preparation method and application thereof

    CN120329025A